Effects of Gamma Radiation Exposure to Hematopoietic Cells on Bone Marrow - Qomariyah, Nurul; Juswono, Unggul P.; Rifaâ€™i, Muhaimin (Natural B, Journal of Health and Environmental Sciences, 2013)
Radiotherapy is a treatment for cancer which use external radiation sources with the aim to damage the DNA in the nucleus of the cancer chromosomes and cause necrosis of cancer cells. The exposure of radiation to the spinal cord as the site of blood cell formation would change the hematopoietic circulation system. The effect of gamma radiation exposure on decreasing of hematopoietic cells quantity is still unknown and it needs further experiment to determine the effect the radiation and the effect of P. niruriÂ  extract giving on the reduction of immune cells quantity which are CD34+ and B220+ cells in the bone marrow. In this experiment, five variations of the dose radiation was used. The dose were 100 rad, 200 rad, 300 rad, 400 rad and 500 rad and use single dose of P. niruri as much 250 mg/kg BB. The dose of 100 rad radiation was given daily and P. niruri extract was given for 14 days before and during radiation. The amount of the CD34+ and B220+ cells is counted and analyzed by Flow cytometry. The result of this experiment showed that the giving of gamma ray irradiation reduced the amount of immune cells in the bone marrow. The increasing radiation dose was caused increasing of the reduction of cells immune quantity. The giving of P.niruri extract inhibits hematopoietic cell through increasing of the absolut amount of CD34+ cell in the bone marrow.